Plant Consumption by Early-Middle Neolithic Peoples in Guangxi, South China: Archaeobotanical Evidence From the Dingsishan Site - Zhang, Xi; Huang, Chao; Zhou, Zhenyu; Olsen, John W.; Huang, Qiang; Guan, Ying (Frontiers in Earth Science, 2022)
Abstract: The Dingsishan Site, located in Nanning City, Guangxi Zhuang Autonomous Region, is one of the most important Neolithic archaeological sites in the Lingnan region of China’s southeastern seaboard. Plant microfossil remains recovered from excavated artifacts and human teeth suggest that the site’s ancient inhabitants practiced a subsistence system based on foraging. Wild plant food resources dominated their vegetal diet. Starch granules extracted from residue samples represent various taxa, including plant roots and tubers, aquatic plant fruits, beans, and wild cereals, defining the primary vegetal diet of Dingsishan’s Neolithic occupants. In addition, residue samples from shell artifacts yielded starch granules and phytolith remains, providing significant clues as to the function of these tools. We also identified millet starch granules from Dingsishan Cultural Phases 3-4 (ca. 7000-6000 BP), albeit in extremely low quantities. Holocene paleoecological conditions in the Lingnan area provided diverse and plentiful wild food resources, allowing the relatively late emergence of agriculture. Our study suggests that Middle Neolithic human groups in the Yong River drainage consumed various plants, and their subsistence pattern was relatively stable through the four Cultural Phases identified at Dingsishan. Our conclusions enhance understanding the diversity of plant food resources exploited by foraging societies and interpretations of differences in patterns of agricultural origins in different ecological regions of China.